1976
DOI: 10.1172/jci108440
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the protease activity in the chemotactic factor inactivator.

Abstract: A B S T R A C T The chemotactic factor inactivator (CFI) isolated from human serum contains a kininase activity that causes extensive hydrolysis of bradykinin. The highly chemotactic synthetic peptide Met-Leu-Phe was completely hydrolyzed by CFI preparations. The release of the constituent amino acids from this peptide coincided with a loss of its chemotactic activity. The Nformyl, but not the amide derivative, of the leukotactic peptide Met-Leu-Phe was resistant to the action of CFI, as evidenced by chemotact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Inactivating agents may be found in serum Chemotactic Factor Inactivation 917 or associated with leukocytes. Normal human serum contains chemotactic factor inactivators which degrade both complement-derived and bacterial chemoattractants (45,46), apparently functioning as aminopeptidases (47). Serum carboxypeptidase B converts C5a to its desarginyl derivative with loss of anaphylatoxic, but not chemotactic activity (40).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivating agents may be found in serum Chemotactic Factor Inactivation 917 or associated with leukocytes. Normal human serum contains chemotactic factor inactivators which degrade both complement-derived and bacterial chemoattractants (45,46), apparently functioning as aminopeptidases (47). Serum carboxypeptidase B converts C5a to its desarginyl derivative with loss of anaphylatoxic, but not chemotactic activity (40).…”
Section: Discussionmentioning
confidence: 99%
“…When these sera were examined for effects on the bacterial chemotactic factor from E. coli, only M. R. serum was found to have inhibitory activity (which was heat labile). It is very likely, therefore, that whereas M. R. serum contained only increased amounts of the previously described heat-labile chemotactic factor inactivator(s) (31)(32)(33), sera from the other four patients contained heat-stable inhibitory activity specifically directed against the C5-derived chemotactic peptide(s) in ZTS. When serum from one of these patients (L. M.) was also subjected to ammonium sulfate fractionation and chromatography on Sephadex G-200, three peaks of inhibitory activity were found which were identical in every respect with the inhibitory activity isolated from R. J. serum (see Fig.…”
Section: Ztsmentioning
confidence: 93%
“…If it unexpectedly has an ability to impair the effects of vasoactive amines, this is probably a moot point, since all studies to date have provided Suppression of Inflammationnegative evidence for the role of vasoactive amines in the Arthus reaction (reviewed in reference 17). Although it has been demonstrated that bradykinin can be inactivated by CFI (6), no statements can be made regarding the role of this kinin in immune complex-induced inflammatory reactions, since no direct and highly specific method for blocking the generation of, or the action of, bradykinin in vivo has yet been devised.…”
Section: Resultsmentioning
confidence: 99%
“…Present in normal human serum is a chemotactic factor inactivator (CFI)' that irreversibly inhibits leukotactic factors, presumably by its aminopeptidase activity (5,6). In humans with increased levels of CFI in the serum, an association has been found with defective expression of inflammatory reactions as maniReceived for publication 15 October 1976 and in revised form 20 January 1977.…”
Section: Introductionmentioning
confidence: 99%